LaSrCo0.5Rh0.5O3.25 and LaSrNi0.5Rh0.5O3.25:topochemically reduced, mixed valence Rh(I)/Rh(III) Oxides - Xu, Z; Palgrave, RG; Hayward, MA (American Chemical Society, 2020)
Topochemical reduction of the n = 1 Ruddlesden-Popper phases LaSrCo0.5Rh0.5O4 and LaSrNi0.5Rh0.5O4 with Zr yields LaSrCo0.5Rh0.5O3.25 and LaSrNi0.5Rh0.5O3.25, respectively. Magnetization and XPS data reveal that while the rhodium centers in LaSrCo0.5Rh0.5O3.25 and LaSrNi0.5Rh0.5O3.25 have an average oxidation state of Rh2+, these are actually mixed valence Rh(I,III) compounds, with the disproportionation of Rh2+ driven by the favorability of locating d8 Rh1+ and d6 Rh3+ cations within square-planar and square-based pyramidal coordination sites, respectively.